Penerapan Integrasi Ilmu Pengetahuan dan Agama Berdasarkan Dalil Al-Qur’an: Studi Kasus di MTs Raudlatul Hasaniyah Mojolegi Gading Probolinggo dengan Fokus pada Teori Big Bang, Embriologi, dan Lapisan Atmosfer - Khairul Anam; Ainur Rofiq Sofa (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This study examines the integration of science and religion based on Quranic verses at MTs Raudlatul Hasaniyah Mojolegi Gading Probolinggo, focusing on the Big Bang theory, embryology, and atmospheric layers. The research investigates how the school implements this integration through training and seminars involving academics, scholars, scientists, and teachers. The aim is to provide deeper insights to educators, students, and the surrounding community about the relationship between scientific discoveries and religious teachings, especially as reflected in Quranic verses. The findings suggest that integrating science and religion enriches students' understanding of both the natural world and the greatness of God, showing that science and religion can complement each other. This approach helps teachers incorporate scientific concepts with religious teachings, fostering a more holistic and contextual understanding among students.